Evolution of trilobite enrolment during the Great Ordovician Biodiversification Event: insights from kinematic modelling. (21st September 2017) - Esteve, Jorge; Gutiérrez‐Marco, Juan Carlos; Rubio, Pedro; Rábano, Isabel
Abstract : The Great Ordovician Biodiversification Event (GOBE) represents a diversification at lower taxonomic levels of most body plans that had appeared during the Cambrian explosion. Among trilobites, several novelties related to enrolment evolved during the GOBE. A kinematic analysis by means of 3D modelling of some new enrolment types shows no relationship with those of the Cambrian trilobites. While some structures emerged for the first time in Ordovician trilobites (e.g. articulations and panderian organs), other structures (e.g. anterior and posterior arch in head and tail) appear earlier in Cambrian trilobites. Our results suggest that the evolution of some groups was clearly rooted in the Cambrian explosion while others clearly appeared during the GOBE.